Liquid crystal polymer and its preparation method, thin film material, microfluidic chip and equipment

By forming a double dynamic covalent network in azobenzene liquid crystal polymer material, the problems of poor material orientation effect and deterioration performance are solved, and higher cyclic performance and photodeformation ability are achieved.

CN119192540BActive Publication Date: 2025-03-18FUDAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411697370.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-18
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The azobenzene liquid crystal polymer material has poor orientation effect during photodeformation, resulting in small photodeformation, insufficient output stress driving liquid transportation, and under the action of cyclic stress or strain, the deformation performance of the material gradually decreases, affecting the stability of the use of composite devices.

Method used

By attaching functional groups, especially furan groups and cinnamate groups, to the backbone of the azobenzene liquid crystal polymer material, a double dynamic covalent network is formed, and the degree of cross-linking and orientation stability of the material are improved.

Benefits of technology

The cyclic performance and photodeformation ability of azobenzene liquid crystal polymer material are improved, the toughness and modulus of the material are enhanced, so that it can show a greater strain value under the action of equal stress, and it can show good self-support during the deformation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192540B_ABST
    Figure CN119192540B_ABST
Patent Text Reader

Abstract

The invention discloses an azobenzene liquid crystal polymer material, which is obtained by cross-linking reaction between an azobenzene liquid crystal polymer material precursor and a cross-linking agent, wherein the cross-linking reaction is a reaction between a furan group on a side chain of the azobenzene liquid crystal polymer material precursor and a cross-linking agent, and the precursor is obtained by ring-opening metathesis polymerization of CAB monomer, CABO monomer and CA monomer, wherein the CAB monomer has a structure shown in formula (I), the CABO monomer has a structure shown in formula (II), the CA monomer has a structure shown in formula (III), and the azobenzene liquid crystal polymer material has a structure shown in formula (IV): during the ring-opening metathesis polymerization reaction, the molar ratio of the CAB monomer, the CABO monomer and the CA monomer is x:y:z, wherein x=3, y=1, and the value range of z is 0.5-3. The liquid crystal material has a more stable orientation, and has better photodeformability and cycle performance. The invention also discloses a polymer material preparation method, a liquid crystal film material and a preparation method, a microfluidic chip and a device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of liquid crystal materials, and in particular to liquid crystal polymers and preparation methods thereof, thin film materials, microfluidic chips and devices. Background Art

[0002] Azobenzene liquid crystal polymers produce photoinduced cis-trans isomerization of azobenzene groups under ultraviolet light, causing the orientation of liquid crystal units to change. This change in the ordered arrangement further causes anisotropic macroscopic deformation of the entire polymer network. Since light stimulation has the characteristics of remote and local precise control, and can be regulated by changing multiple parameters such as wavelength, intensity, and polarization direction, photodeformable liquid crystal polymers have unique advantages in the preparation of wireless soft machines. At present, soft machines constructed based on photodeformable liquid crystal polymers already have functions such as microfluidic transport and visual photosensitivity recognition, and have broad application prospects in wearable devices and biomedicine.

[0003] In order to obtain reversible deformation capability, azobenzene liquid crystal polymers usually need to construct a chemical cross-linking network to fix the orderly orientation of the liquid crystal unit while aligning the liquid crystal unit. This makes azobenzene liquid crystal polymers unsuitable for processing and molding of general polymers, and difficult to process into three-dimensional structures; in addition, due to the existence of a chemical cross-linking network, azobenzene liquid crystal polymers are difficult to combine with other substrate materials to construct composite devices, and after molding, they are insoluble and infusible, making them difficult to recycle and reuse.

[0004] Chinese patent document CN103087296A discloses a side-chain linear azobenzene liquid crystal polymer material and a preparation method thereof. The side-chain linear azobenzene liquid crystal polymer material is synthesized by ring-opening metathesis polymerization using a Grubbs catalyst and a cyclooctene derivative (CAB) as a monomer. The polymer material has a polymer main chain similar to rubber, and the side chain carries a photoresponsive azobenzene liquid crystal unit. The material still has rubber elasticity without a cross-linked network structure, and has good photoresponsive properties. After being dissolved in a solvent or heated and melted, the side-chain linear azobenzene liquid crystal polymer material can be directly processed and molded by a common processing method to prepare a photoresponsive liquid crystal polymer material. The size and shape of the processing molding are unlimited, and it can be recycled and reused after molding. It is a new type of low-carbon and environmentally friendly photoresponsive liquid crystal polymer material. This material is bonded to a PMMA substrate engraved with a flow channel to achieve light-controlled fluid transportation. Moreover, due to its linear molecular structure, the liquid crystal polymer material can be bonded to the substrate without glue, effectively avoiding the damage of the fine microchannel structure morphology required for microfluidics by the added adhesive during the construction of the composite device, and also simplifying the steps of preparing the composite device.

[0005] However, this photodeformable high molecular weight linear liquid crystal polymer material only aligns the liquid crystal unit through annealing self-assembly, and the liquid crystal unit orientation effect is poor, the generated photoinduced strain is small, and the output stress to drive liquid transport is insufficient. In addition, the liquid crystal polymer with molecular chain entanglement as the physical cross-linking network is prone to molecular chain slip during the deformation process. Under the action of cyclic stress or strain, the deformation performance of the material gradually decreases. After a certain number of cycles, the material completely loses the ability to respond to deformation, and affects the stability of the composite device.

[0006] One way to solve the above problem is to further modify the azobenzene liquid crystal polymer material through other groups, and improve the performance of the material by attaching functional groups to the main chain. Therefore, on the basis of the main chain structure, it is necessary to select the groups and design the structure so that the functions of the main chain and side chain groups can be fully exerted. In addition, if the groups are simply attached, different groups may interfere with each other, which will not only fail to improve the performance of the material, but may even affect the original basic functions of the material. In addition, the more types of groups attached, the more complex the influence of the groups on the azobenzene liquid crystal polymer material, especially in terms of structure and orientation. If improperly adjusted, it will have a negative effect on various behaviors of the polymer material, thereby affecting the application of the polymer material. Summary of the invention

[0007] In order to solve the above technical problems, the embodiment of the present invention discloses an azobenzene liquid crystal polymer material. The azobenzene liquid crystal polymer material is obtained by a cross-linking reaction between an azobenzene liquid crystal polymer material precursor and a cross-linking agent. The cross-linking reaction is a reaction between the furan group on the side chain of the azobenzene liquid crystal polymer material precursor and the cross-linking agent. The azobenzene liquid crystal polymer material precursor is obtained by a ring-opening metathesis polymerization reaction between a CAB monomer, a CABO monomer and a CA monomer. The CAB monomer has a structure shown in formula (I), the CABO monomer has a structure shown in formula (II), the CA monomer has a structure shown in formula (III), and the azobenzene liquid crystal polymer material has a structure shown in formula (IV):

[0008] (I);

[0009] (II); (III);

[0010] (IV);

[0011] When performing the ring-opening metathesis polymerization reaction, the molar ratio of the CAB monomer, the CABO monomer and the CA monomer is x:y:z, wherein x=3, y=1, and the value range of z is 0.5-3.

[0012] By adopting the above technical scheme, various groups in the azobenzene liquid crystal polymer material can fully play their roles, thereby improving the cycle performance and photoinduced deformation ability of the azobenzene liquid crystal polymer material when used as a liquid crystal material, and the groups will not have adverse effects on various behaviors of the azobenzene liquid crystal polymer material, thereby ensuring the applicability and stability of the azobenzene liquid crystal polymer material.

[0013] Optionally, the azobenzene liquid crystal polymer material precursor has a structure shown in formula (V):

[0014] (V).

[0015] Optionally, the cross-linking agent has a structure as shown in formula (VI):

[0016] (VI).

[0017] According to another specific embodiment of the present invention, the embodiment of the present invention discloses a method for preparing an azobenzene liquid crystal polymer material, comprising the following steps:

[0018] Ring-opening polymerization: CAB monomer, CABO monomer, CA monomer and Grubbs II generation catalyst are mixed to carry out ring-opening polymerization to generate azobenzene liquid crystal polymer material precursor;

[0019] Cross-linking polymerization: The azobenzene liquid crystal polymer material precursor is mixed with a cross-linking agent, and the azobenzene liquid crystal polymer material is obtained after a cross-linking reaction.

[0020] By adopting the above technical solution, the feed ratio of various monomers can be controlled in the ring-opening polymerization step, thereby obtaining an azobenzene liquid crystal polymer material in which each group can fully exert its function.

[0021] Optionally, in the ring-opening polymerization step, after the CAB monomer, the CABO monomer, the CA monomer, the Grubbs II generation catalyst and the solvent are mixed, the total concentration of the CAB monomer, the CABO monomer and the CA monomer is 0.8-1.2 mmol / mL, and the molar ratio of the CAB monomer, the CABO monomer and the CA monomer to the Grubbs II generation catalyst is 900:1-1000:1.

[0022] According to another specific embodiment of the present invention, the embodiment of the present invention discloses a liquid crystal film material, and the liquid crystal film material is made of the above-mentioned azobenzene liquid crystal polymer material.

[0023] By adopting the above technical solution, the photoinduced deformation amplitude and cycle performance of azobenzene liquid crystal film materials can be effectively improved.

[0024] Optionally, the liquid crystal film material bends and deforms under ultraviolet light with a wavelength of 365nm, and recovers to its original state under green light with a wavelength of 530nm. After 300 cycles of bending and deformation-restoration, the bending deformation amount of the liquid crystal film material remains unchanged.

[0025] The embodiment of the present invention further discloses a method for preparing a liquid crystal film material, comprising the following steps:

[0026] Stress field orientation: placing a film made of the azobenzene liquid crystal polymer material on a mold with a curved surface, so that the azobenzene liquid crystal polymer material is oriented in a stress field;

[0027] Photocrosslinking and orientation: The film made of the azobenzene liquid crystal polymer material is irradiated with ultraviolet light with a wavelength of 312nm for photocrosslinking and orientation to obtain the liquid crystal film material. The above technical solution can be used to orient the liquid crystal film material under the action of the stress field to avoid mutual interference between groups.

[0028] Optionally, the intensity of the ultraviolet light is 20 mW / cm 2 -80mW / cm 2 .

[0029] According to another specific embodiment of the present invention, an embodiment of the present invention discloses a microfluidic chip, comprising:

[0030] A substrate, comprising an injection port and a groove communicating with the injection port;

[0031] A liquid crystal polymer film material, made from the above-mentioned azobenzene liquid crystal polymer material and attached to the substrate;

[0032] The liquid crystal polymer film material at least partially covers the groove to form a closed channel with the groove, so that the microfluid can be driven through the closed channel under the Laplace pressure difference generated by the asymmetric photoinduced deformation of the closed channel.

[0033] By adopting the above technical solution, the efficiency and accuracy of detection can be improved and the service life can be extended.

[0034] According to another specific embodiment of the present invention, an embodiment of the present invention discloses a microfluidic device, including the above-mentioned microfluidic chip.

[0035] By adopting the above technical solution, the efficiency and accuracy of detection can be improved and the service life can be extended. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 A schematic diagram showing the phase transition characteristics of the azobenzene liquid crystal polymer material according to Example 1 of the present invention;

[0037] Figure 2 A schematic diagram showing the phase transition characteristics of the azobenzene liquid crystal polymer material according to Example 2 of the present invention;

[0038] Figure 3 A schematic diagram showing the phase transition characteristics of the azobenzene liquid crystal polymer material according to Example 3 of the present invention;

[0039] Figure 4 A schematic diagram showing the phase transition characteristics of the azobenzene liquid crystal polymer material according to Example 4 of the present invention;

[0040] Figure 5 A schematic diagram showing a preparation process of a liquid crystal thin film material according to an embodiment of the present invention;

[0041] Figure 6 The photographs show that the liquid crystal film material of comparative example 1 of the present invention is bent and deformed under 365nm ultraviolet light and recovers its deformation under 530nm green light;

[0042] Figure 7 Photos showing that the liquid crystal film material of Application Example 1 of the present invention is bent and deformed under 365nm ultraviolet light and recovers its deformation under 530nm green light;

[0043] Figure 8 A photograph showing the liquid crystal film material of Application Example 2 of the present invention being bonded to a PMMA substrate without adhesive. DETAILED DESCRIPTION

[0044] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this implementation. On the contrary, the purpose of introducing the invention in conjunction with the implementation is to cover other options or modifications that may extend based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0045] It should be noted that in this specification, similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings.

[0046] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.

[0047] The term "liquid crystal film material" mentioned in the context of the present invention is usually made by drop coating and orientation of liquid crystal polymer materials, and the thickness of the liquid crystal film material is about 40-70μm. For example, a liquid crystal film material is formed by drop coating and orientation of azobenzene liquid crystal polymer materials. The liquid crystal film material can achieve reversible deformation under alternating irradiation of ultraviolet light and green light, and has functional characteristics. When this liquid crystal film material is compounded with a PMMA substrate (polymethyl methacrylate, Polymethyl Methacrylate, PMMA for short) engraved with microchannels, it can be used to prepare optical microfluidic chips. Under light conditions, the liquid crystal film material produces gradient deformation, and then forms a Laplace pressure difference in the microchannel to drive the movement of droplets, thereby realizing optically controlled multi-layer fluid manipulation without the need for external pumps and valves.

[0048] Azobenzene molecules and their derivatives are one of the common optical switch molecules in liquid crystal materials. Azobenzene molecules and their derivatives can undergo isomerization reactions under light. Trans-azobenzene has a rod-like structure, has good compatibility with liquid crystal molecules, and usually presents a liquid crystal state. The structure of cis-azobenzene is curved, which is incompatible with rod-like liquid crystal molecules, thus destroying the stable liquid crystal phase. When azobenzene is introduced into liquid crystal elastomers, the trans-cis isomerization process at the molecular level can effectively regulate the arrangement of molecules in the elastomer and induce photomechanical drive from order to disorder through thermal and photochemical means.

[0049] However, azobenzene liquid crystal polymer materials have the problems of difficult processing and recycling, which affect their application. Chinese patent document CN103087296A discloses a side chain linear azobenzene liquid crystal polymer material, whose chemical structure is a butadiene-ethylene-functional group substituted ethylene ternary alternating polymer as the main chain, and uses a cyclooctene derivative monomer (monomer CAB, structure: ), a side-chain linear azobenzene liquid crystal polymer material was synthesized by ring-opening metathesis polymerization. This polymer material has a polymer main chain similar to rubber, has the advantages of a polyolefin system, and has a photoresponsive azobenzene liquid crystal unit on the side chain. The material still has rubber elasticity without a cross-linked network structure, and has good photoresponsive properties. After being dissolved in a solvent or heated and melted, this side-chain linear azobenzene liquid crystal polymer material can be directly processed and molded by common processing methods to prepare a photoresponsive liquid crystal polymer material. The size and shape of the processing are unlimited, and it can be recycled and reused after molding.

[0050] However, the liquid crystal polymer material disclosed in Chinese patent document CN103087296A has poor liquid crystal unit orientation effect, generates small photoinduced strain, and has limited driving ability. Moreover, after a certain number of cycles, the deformation performance of the material decreases significantly, or even completely loses the ability to respond to deformation.

[0051] Since this material has the advantages of a polyolefin system, good processing performance, and can be recycled, if the original performance advantages of the material can be retained and further optimized on this basis, the application value of azobenzene liquid crystal polymer materials will be greatly improved. In other words, the main chain structure and the corresponding structure of the CAB monomer of the azobenzene liquid crystal polymer material can be retained, and on this basis, the azobenzene liquid crystal polymer material is improved to solve the above problems.

[0052] First of all, regarding how to increase the strain value, the most direct way is to increase the degree of cross-linking of the structure, which can improve the toughness and modulus of the material, and the mechanical properties can be improved. However, if cross-linking is performed directly on the main chain or side chain of the original structure, the main chain structure of the molecule and the corresponding structure of the CAB monomer will be affected, and the characteristics of the original linear structure cannot be retained. Therefore, considering these situations, a structure that does not affect the original linear structure and can improve cross-linking should be constructed. Similarly, in order to improve the orientation effect of the material, it should also be considered how to prevent adverse effects on the original structure and try to maintain the original structure. Moreover, no matter what modifications are made to the structure, it is still necessary to maintain the basic performance of azobenzene liquid crystal polymer materials and the advantages of recyclability while ensuring its processability.

[0053] Therefore, in view of the above circumstances, the first aspect of the present invention discloses an azobenzene liquid crystal polymer material, which is obtained by a cross-linking reaction between an azobenzene liquid crystal polymer material precursor and a cross-linking agent. The cross-linking reaction is a reaction between the furan group on the side chain of the azobenzene liquid crystal polymer material precursor and the cross-linking agent. The azobenzene liquid crystal polymer material precursor is obtained by a ring-opening metathesis polymerization reaction of a CAB monomer, a CABO monomer and a CA monomer. The CAB monomer has a structure shown in formula (I), the CABO monomer has a structure shown in formula (II), and the CA monomer has a structure shown in formula (III):

[0054] (I);

[0055] (II); (III).

[0056] It can be seen that CAB monomer, CABO monomer and CA monomer all have cyclooctene groups. Thus, after the ring-opening metathesis polymerization reaction, the cyclooctene groups of each monomer open to form a main chain, ensuring that the main chain has a three-member alternating polymer structure of butadiene-ethylene-functional group substituted ethylene, maintaining the advantages of the original main chain system. Specifically, through the ring-opening metathesis polymerization reaction, three different side chain groups can be formed on the main chain, which are formed by CAB monomer, CABO monomer and CA monomer respectively.

[0057] Further, it can be seen from the monomer structure that the CABO monomer can form an azobenzene group substituted by a furan group. By blending with an external crosslinker, the conjugated double bonds on the furan ring can react specifically with the crosslinker to form a certain crosslinked structure, giving the polymer good toughness and appropriate modulus, so that the material can show a larger strain value under the same stress, and at the same time show good self-support during the deformation process. By crosslinking specific groups, the linear morphology of the main chain structure and the corresponding structure of the CAB monomer can be kept unaffected. In addition, the furan group is connected to the azobenzene group. Compared with simply connecting the furan group to the main chain, this connection method can further highlight the special properties of the azobenzene polymer. In addition, if the furan group is directly connected to the main chain, due to the short length of the furan group and the small overall volume, it may be interfered by the groups of other side chains, that is, the reaction of the furan group with the crosslinker is affected, and crosslinking cannot be fully performed, and the strain capacity is insufficiently improved. Furthermore, the crosslinking agent is maleimide, and the conjugated double bonds on the furan ring react with the double bonds of the crosslinking agent to form a dynamic Diels-Alder (DA) network. The breakage-reconstruction equilibrium of the DA bond will shift toward the direction of bond breaking or bonding, and has the thermally reversible properties of low-temperature bonding and high-temperature bond breaking, which can be flexibly regulated. Therefore, the polymer containing the DA dynamic network can not only achieve stress relaxation through topological rearrangement, but also reduce the crosslinking network density by increasing the temperature, so that the polymer has processing properties similar to those of linear polymers, and the polymer can be recycled and reprocessed by the melt method or solution method. Therefore, the choice of using CABO monomers to construct the side chain structure is a trade-off and consideration under multiple factors. It will not affect the basic structure and properties of the material itself, ensure its processability and reprocessability, and bring greater strain values ​​and mechanical properties to the material.

[0058] Furthermore, the addition of CA monomers can form cinnamate group side chains on the main chain. The cinnamate group will undergo a cycloaddition reaction under the irradiation of 312 nm ultraviolet light to form a dimer, and will depolymerize under the irradiation of 254 nm ultraviolet light. Therefore, the density of the cross-linked network of the azobenzene liquid crystal polymer can also be adjusted by light. This kind of photocrosslinking can make the azobenzene liquid crystal polymer material have a more stable orientation.

[0059] That is to say, the azobenzene liquid crystal polymer material is copolymerized by a ring-opening metathesis polymerization method, and three liquid crystal monomers with a flexible carbon chain at the tail end, a furan group at the tail end, and a cinnamate group at the tail end are synthesized to synthesize a series of linear liquid crystal copolymers, namely, azobenzene liquid crystal polymer material precursors. It can not only ensure the basic performance of the azobenzene liquid crystal polymer material, but also form two different dynamic cross-linking networks. The cinnamate network formed by photocrosslinking fixes the orientation of the liquid crystal primitives, and the mechanical properties of the polymer are ensured by the DA network. Due to the use of a covalent cross-linking network to fix the liquid crystal orientation, the cycle performance has been significantly improved. The introduction of the DA network gives the polymer good toughness and appropriate modulus, so that the polymer can show a larger strain value under the same stress, and at the same time show good self-support during the deformation process. In summary, the introduction of the dual dynamic covalent network effectively improves the photoinduced deformation amplitude and cycle performance of the azobenzene liquid crystal polymer. In addition, the azobenzene liquid crystal polymer material can reduce the crosslinking density of the DA dynamic network by increasing the temperature under the premise that the cinnamate crosslinking network fixes the liquid crystal orientation, so that the polymer exhibits adhesion characteristics similar to those of a linear polymer, which is convenient for combining with substrate materials of other materials to construct a composite device. Therefore, although crosslinking occurs, it will not affect the processing performance. Both dynamic covalent networks can be dissociated after molding, making the azobenzene liquid crystal polymer material recyclable and reusable. Due to the different types of stimulus sources, the properties of the two dynamic networks can also be independently controlled. While retaining the original structural advantages, the azobenzene liquid crystal polymer material has achieved significant performance improvements.

[0060] However, it was found in the study that when preparing azobenzene liquid crystal polymer materials, it is not just a simple mixture of the above three monomers and the corresponding reaction to obtain a material with the desired properties. In fact, since three different side chains are formed at the same time, they have different structures and properties, and the control is relatively complicated. On the one hand, the introduction of a variety of different side chains in the polymer material will increase the complexity of the structure and potential mutual interference. Each side chain may have different chemical properties and space requirements, which may lead to undesirable intermolecular forces and uneven molecular morphology, thereby affecting the overall performance of the material. Different groups are very likely to interfere with each other, which may lead to the inability to achieve the expected effect, and even the basic functions will be affected. On the other hand, for the three functional primitives of the present invention, their ratio regulation is very critical, and the ratio will have an important impact on their functional realization. For example, if the content of CA monomer is too high, the material has low liquid crystallinity, and the deformation ability will drop sharply or even disappear. If the content of CA monomer is too low, the photocrosslinking performance will be lost. However, it is not easy to accurately regulate the ratio of the three groups. The present invention adopts a ring-opening metathesis polymerization method, and the regulation ratio can be changed by changing the feed ratio. Furthermore, after a large number of experiments, it was found that by controlling the feed ratio, an azobenzene liquid crystal polymer material in which the side chains do not interfere with each other and the structure is stable can be obtained, and the role of each functional unit can be fully and effectively exerted, and the coordination is good, and finally an azobenzene liquid crystal polymer material that is easy to process, recyclable, has good cycle performance, stable orientation, and a large photoinduced deformation amplitude is obtained. Specifically, when performing a ring-opening metathesis polymerization reaction, the feed molar ratio of CAB monomer, CABO monomer, and CA monomer is x:y:z, wherein x=3, y=1, and the value range of z is 0.5-3. Within the feed ratio range, a suitable structure can be obtained, and the main chain and each side chain of the azobenzene liquid crystal polymer material can fully exert their respective functions, will not interfere with the function of other structures, and the functions are fully exerted, with good synergistic effects, and the performance of the azobenzene liquid crystal polymer material is jointly improved.

[0061] Moreover, changes in the feed ratio have a significant effect on the phase transition temperature. This may be due to changes in the structure and orientation of the polymer chain caused by different feed ratios, which in turn affects the phase behavior of the azobenzene liquid crystal polymer material. If the phase transition temperature is too high, the azobenzene liquid crystal polymer material may not be able to maintain the liquid crystal phase state within the normal operating temperature in practical applications, resulting in reduced optical performance, such as poor display effects, or blurring when the temperature changes. If the phase transition temperature is too low, the azobenzene liquid crystal polymer material is in a liquid crystal state at room temperature, which may make the material easily lose stability during temperature fluctuations, resulting in inconsistent performance.

[0062] Specifically, after the ring-opening metathesis polymerization reaction of CAB monomer, CABO monomer and CA monomer, an azobenzene liquid crystal polymer material precursor is obtained, and the azobenzene liquid crystal polymer material precursor has a structure shown in formula (V). Specifically, the azobenzene liquid crystal polymer material precursor already has the main chain structure of the azobenzene liquid crystal polymer material, and forms three different side chains, and all of them are linear structures, which are easy to react and process in the subsequent reaction, and the three side chains do not interfere with each other, and the reaction and processing efficiency is higher.

[0063] (V).

[0064] More specifically, the azobenzene liquid crystal polymer material has a structure as shown in formula (IV), and the cross-linking agent has a structure as shown in formula (VI):

[0065] (IV);

[0066] (VI).

[0067] The main chain of the azobenzene liquid crystal polymer material is a ternary alternating polymer structure of butadiene-ethylene-functional group substituted ethylene, which makes the azobenzene liquid crystal polymer material have good processing performance. At the same time, it also has three different linear side chain structures, which also makes the azobenzene liquid crystal polymer material suitable for processing. Although the furan group is cross-linked with the cross-linking agent, the degree of cross-linking is controllable and will not affect the processing performance of the azobenzene liquid crystal polymer material. The addition of CABO monomer and the corresponding structure of CA monomer forms a dual dynamic covalent network, which can further enable the azobenzene liquid crystal polymer material to achieve excellent orientation effect and photoinduced deformation amplitude, and the performance is stable and reliable. The dual dynamic covalent network can be dissociated after molding, combined with the linear structure, so that the azobenzene liquid crystal polymer material can be recycled and reused. Under the joint action of the main chain and the side chain, the azobenzene liquid crystal polymer material can have multiple performances.

[0068] The second aspect of the present invention discloses a method for preparing an azobenzene liquid crystal polymer material, comprising the following steps:

[0069] Ring-opening polymerization: CAB monomer, CABO monomer, CA monomer and Grubbs II generation catalyst are mixed to carry out ring-opening polymerization to generate azobenzene liquid crystal polymer material precursor;

[0070] Cross-linking polymerization: The azobenzene liquid crystal polymer material precursor is mixed with a cross-linking agent, and the azobenzene liquid crystal polymer material is obtained after a cross-linking reaction.

[0071] This method can conveniently achieve proportion regulation and structural control of each functional unit by controlling the feed ratio in ring-opening metathesis polymerization, and can also form a cross-linked structure through specific cross-linking polymerization, thereby improving the mechanical properties of the material without affecting the basic structure.

[0072] Further, the total concentration of CAB monomer, CABO monomer and CA monomer is 0.8-1.2 mmol / mL, and the molar ratio of CAB monomer, CABO monomer and CA monomer to Grubbs II catalyst is 900:1-1000:1. That is, the ratio of the total molar amount of CAB monomer, CABO monomer and CA monomer to the molar amount of Grubbs II catalyst is 900:1-1000:1. Specifically, the solvent can be CH2Cl2, for example. At a monomer concentration of 0.8-1.2 mmol / mL, the molar ratio of CAB monomer, CABO monomer and CA monomer to Grubbs II catalyst is controlled to be 900:1-1000:1, which can further ensure that a linear polymer precursor is obtained, which is convenient for subsequent processing, and can ensure that the molecular weight of the polymer is appropriate, thereby ensuring that the mechanical properties of the film sample obtained later are good. Due to the use of the active polymerization method, the proportion of polymer functional units can be conveniently adjusted by changing the monomer feed ratio, thereby adjusting the liquid crystallinity and phase transition temperature of the linear polymer. Preferably, the total concentration of CAB monomer, CABO monomer and CA monomer is 1 mmol / mL, and the molar ratio of CAB monomer, CABO monomer and CA monomer to Grubbs II generation catalyst is 1000:1, so that the reaction is more sufficient and controllable. More preferably, the ring-opening metathesis polymerization is carried out in an anhydrous and oxygen-free environment. "Anhydrous and oxygen-free" means that water and oxygen need to be excluded as much as possible to ensure the stability of the catalyst and monomers and promote the smooth progress of the polymerization reaction, for example, by using a dry solvent such as anhydrous CH2Cl2, and reacting under vacuum conditions.

[0073] Specifically, the method for preparing the azobenzene liquid crystal polymer material includes the following steps.

[0074] (1) Preparation of CAB monomer: The synthetic route is as follows. The preparation method thereof is referred to Chinese patent document CN103087296A.

[0075] .

[0076] (2) Preparation of CABO monomer: The synthetic route is as follows:

[0077] .

[0078] More specifically, the synthesis methods of the intermediates and CABO monomers are as follows:

[0079] Synthesis of intermediate M1: Add p-aminobenzoic acid (4.11 g, 30 mmol) to a 500 mL eggplant-shaped flask and dissolve it in 25 mL of dilute hydrochloric acid (H2O: HCl = 3: 1 (v: v)). Then slowly add 15 mL of sodium nitrite aqueous solution (2 mol / L) in an ice-water bath and stir for 30 min. Add sodium hydroxide (1.2 g, 30 mmol) and phenol (2.82 g, 30 mmol) to 15 mL of distilled water, dissolve them by ultrasonic and pour them into the reaction system. Then add sodium hydroxide solution (1 mol / L) to adjust the pH value of the system to greater than 9, and continue the reaction for 3 h. Add dilute hydrochloric acid (HCl: H2O = 1: 3 (v: v)) to adjust the pH of the reaction solution to about 4. After filtration, dry the product to remove moisture to obtain an orange powder product M1 (5.2 g, yield 70%).

[0080] Synthesis of intermediate M2: Solid M1 (4.8 g, 20 mmol) and potassium carbonate (5.5 g, 40 mmol) were added to a 500 mL eggplant-shaped bottle, and a mixed solution of ethanol and water (40 mL ethanol + 20 mL water) was added to dissolve. The temperature of the water bath was raised to 80 °C, and after the liquid was condensed and refluxed, 11-bromo-1-undecanol (5.6 g, 21 mmol) and a catalytic amount of potassium iodide were added to the reaction solution, and the reaction was continued for 3 h. After that, the temperature was cooled to room temperature, 500 mL of ice water was prepared, and the reaction solution was poured into it and stirred thoroughly. The precipitated orange-yellow solid was filtered to remove water to obtain an orange powder product M2 (6.7 g, yield 82%).

[0081] Synthesis of intermediate M3: Solid M2 (8.2 g, 20 mmol), furfuryl alcohol (2.0 g, 21 mmol), and DMAP (2.4 g, 20 mmol) were added to a 500 mL eggplant-shaped bottle, and 120 mL CH2Cl2 solution was added to dissolve the solid. Dehydrating agent EDC (7.7 g, 40 mmol) was dissolved in 50 mL CH2Cl2, added dropwise to the reaction system, and reacted at room temperature for 48 h. After the reaction, silica gel powder was added to the reaction solution and dried under reduced pressure, and column chromatography was performed using CH2Cl2 as the developing solvent to obtain orange crystalline product M3 (5.0 g, yield 70%).

[0082] Synthesis of CABO monomer: M3 (0.70 g, 2 mmol), 5-succinate-1-cyclooctene (0.68 g, 3 mmol) and DMAP (0.25 g, 2 mmol) were added to a 250 mL eggplant-shaped bottle, and 60 mL CH2Cl2 solvent was added to dissolve the solid. Dehydrating agent EDC (1.15 g, 6 mmol) was dissolved in 30 mL CH2Cl2, added dropwise to the reaction system, and reacted at room temperature for 24 h. After the reaction, silica gel powder was added to the reaction solution and dried under reduced pressure. The dried powder was subjected to column chromatography using CH2Cl2 as the developing solvent. The separated product solution was spin-dried, and then methanol solution was added for recrystallization. After filtration and drying, orange crystalline solid CABO (0.84 g, yield 75%) was obtained.

[0083] (3) Preparation of CA monomer: The synthetic route is as follows:

[0084] .

[0085] More specifically, the synthesis method of CA monomer is as follows: 3.0 g of solid 4-hydroxycyclooctene, 4.2 g of cinnamic acid, and 2.9 g of DMAP are added to a 250 mL eggplant-shaped bottle, and then 50 mL of CH2Cl2 solution is added to dissolve the solid. 9.1 g of dehydrating agent EDC is dissolved in 50 mL of CH2Cl2, added dropwise to the reaction system, and reacted at 50 °C for 24 h. After the reaction is completed, silica gel powder is added to the reaction solution and dried under reduced pressure, and column chromatography is performed using CH2Cl2 as a developing agent to obtain white oily liquid CA (3.5 g, yield 57.4%).

[0086] (4) CAB monomer, CABO monomer and CA monomer are used for ring-opening polymerization to obtain azobenzene liquid crystal polymer material precursor (L-PCABxOyCAz). The synthesis route is as follows:

[0087] .

[0088] The molar ratio of CAB monomer, CABO monomer and CA monomer is x:y:z, and x=3, y=1, and the value range of z is 0.5-3. It should be noted that ROMP (Ring-Opening Metathesis Polymerization) refers to ring-opening metathesis polymerization, and CAB monomer, CABO monomer and CA monomer are obtained by ring-opening metathesis polymerization to obtain azobenzene liquid crystal polymer material precursor.

[0089] A more specific description is given by taking the molar ratio of CAB monomer, CABO monomer, and CA monomer as 3:1:1 as an example. CABO monomer (0.1 g, 0.2 mmol) and CAB monomer (0.375 g, 0.6 mmol) are added to a 10 mL Hiddink bottle, and vacuum-nitrogen-vacuum is repeated three times. In an anhydrous and oxygen-free environment, 0.8 ml of anhydrous CH2Cl2 dissolved in CA monomer (0.051 g, 0.2 mmol) is injected into the Hiddink bottle with a syringe, and then 0.2 mL (1 mg / mL) of CH2Cl2 solution dissolved in Grubbs II generation catalyst is injected, and the reaction is carried out at 45 °C for 2 h. After the polymerization reaction is completed, 10 mL of CH2Cl2 is added to the Hiddink bottle, and the solution is dropped into methanol for precipitation. After filtration, an orange-yellow solid product (0.489 g, 93%) is obtained.

[0090] Among them, the Grubbs II generation catalyst structure is:

[0091] .

[0092] Furthermore, the molar feed ratios of the three monomers can be adjusted to 3:1:0.5, 3:1:1, 3:1:2, and 3:1:3, respectively, and further polymerization can be performed to obtain a series of linear azobenzene liquid crystal copolymers L-PCABxOyCAz.

[0093] (5) The ring-opening polymerization product (i.e., azobenzene liquid crystal polymer material precursor L-PCABxOyCAz) is mixed with a crosslinking agent to obtain an azobenzene liquid crystal polymer material (C-PCABxOyCAz) after a crosslinking reaction. The synthesis route is as follows:

[0094] .

[0095] More specifically, 60 mg / L L-PCABxOyCAz was taken and a toluene solution with a concentration of 6 wt% was prepared. After the linear polymer L-PCABxOyCAz was completely dissolved, it was filtered using a 1 mL syringe with a filter plug. The filtered L-PCABxOyCAz solution was mixed with the cross-linking agent in a molar ratio of 1:1.1 and stirred evenly by a magnetic stirrer.

[0096] More specifically, after stirring, the mixed solution can be directly drop-coated onto a 4 cm×4 cm glass substrate to obtain a thin film product, which is convenient for subsequent processing into a liquid crystal film material. After the solution is fully spread, the toluene solvent is evaporated at a suitable temperature to form a film. After annealing and crosslinking at 80 °C for 3 h, the film is then immersed in ethanol to fall off, and an azobenzene liquid crystal polymer material C-PCABxOyCAz film (thickness of about 50 µm) with a DA dynamic crosslinking network can be obtained.

[0097] The third aspect of the present invention discloses a liquid crystal film material, which is made from the above-mentioned azobenzene liquid crystal polymer material.

[0098] The fourth aspect of the present invention discloses a method for preparing a liquid crystal film material, comprising the following steps:

[0099] Stress field orientation: placing a film made of azobenzene liquid crystal polymer material on a mold with a curved surface, so that the azobenzene liquid crystal polymer material is oriented in a stress field;

[0100] Photo-crosslinking and orientation: A film made of azobenzene liquid crystal polymer material is irradiated with ultraviolet light with a wavelength of 312 nm for photo-crosslinking and orientation to obtain a liquid crystal film material.

[0101] Here, "film made of azobenzene liquid crystal polymer material" refers to the azobenzene liquid crystal polymer material further made into a film-shaped product using a glass substrate, so as to facilitate subsequent cross-linking and processing into the desired liquid crystal film material. Specifically, Figure 5 As shown, a mold with a curved surface can be used or a mold with a curved surface can be modeled and printed. The mold can be a structure in which a triangular prism deformation body is protruding from a rectangular parallelepiped. The triangular prism deformation body is a structure in which one edge of the triangular prism is deformed into a protruding curved surface with an arc. When the azobenzene liquid crystal polymer material has been made into a film during the cross-linking process, the azobenzene liquid crystal polymer material can be directly attached to the curved surface. Subsequently, the film is photo-cross-linked by 312nm ultraviolet light to obtain a dual dynamic network azobenzene liquid crystal polymer film that can undergo photoinduced deformation.

[0102] In fact, the azobenzene element absorbs mainly at 365nm, but it also absorbs at 312nm. That is to say, during the photocrosslinking process, if 312nm ultraviolet light is directly irradiated, the orientation of the azobenzene liquid crystal unit will be disturbed to a certain extent, and the orientation effect will be affected, and the cinnamate group will not be able to play its function. Therefore, although the azobenzene liquid crystal polymer material has been prepared, in the process of further preparing liquid crystal film materials, the problem of light interference still needs to be solved in order to fix the orientation of the azobenzene liquid crystal unit through the cinnamate group.

[0103] As for how to solve the problem of light interference, it is necessary to maintain the structure of the azobenzene liquid crystal polymer material, otherwise it will affect the liquid crystal film material produced. In this case, consider solving the problem by external intervention. Therefore, combining the structure and deformation characteristics of the azobenzene liquid crystal unit, using a mold with a curved surface, first put the azobenzene liquid crystal polymer material on the mold, that is, put the azobenzene liquid crystal polymer material in a stress field. Due to the stress field induced orientation, it can reduce light interference and help improve the orientation effect of the liquid crystal unit. The liquid crystal unit that obtains an ordered orientation induced by stress is fixed by the formed cinnamate cross-linking network to obtain the target dual dynamic covalent network liquid crystal film material.

[0104] Since the azobenzene liquid crystal polymer material has been made into a film during the cross-linking process, the azobenzene liquid crystal polymer material can be directly attached to the curved surface during the stress field and light orientation, which is convenient for operation. In addition, due to the recyclable nature of the material, the film can be processed by solution dissolution, heating and melting, etc., and can be made into polymer films, fibers or other materials with three-dimensional structures, suitable for different application scenarios.

[0105] In a specific embodiment of the present invention, the intensity of the ultraviolet light is 20 mW / cm 2 -80mW / cm 2 Preferably, the light intensity is 50 mW / cm 2 The use of low-intensity ultraviolet light can further reduce the interference with the azobenzene element. At the same time, due to the combination of stress field effect, the orientation effect is not reduced.

[0106] In a specific embodiment of the present invention, the liquid crystal film material prepared by this method bends and deforms under the irradiation of ultraviolet light with a wavelength of 365nm, and the liquid crystal film material returns to its original state under the irradiation of green light with a wavelength of 530nm. After 300 cycles of bending, deformation and restoration, the bending deformation amount of the liquid crystal film material remains unchanged.

[0107] The dual dynamic covalent network liquid crystal film material regulates the orientation of the liquid crystal unit through the stress field, fixes the orientation of the liquid crystal unit through the cinnamate network formed by photocrosslinking, and ensures the mechanical properties of the polymer through the DA network. Due to the application of stress field induced orientation, the orientation effect of the liquid crystal unit is improved to a certain extent. Due to the use of a covalent crosslinking network to fix the liquid crystal orientation, the cycle performance is significantly improved. The introduction of the DA network gives the polymer good toughness and appropriate modulus, so that the polymer can show a larger strain value under the same stress, and at the same time show good self-support during the deformation process.

[0108] In summary, the introduction of dual dynamic covalent networks effectively improves the photoinduced deformation amplitude and cycle performance of liquid crystal film materials. In addition, the liquid crystal film material can reduce the crosslinking density of the DA dynamic network by increasing the temperature under the premise that the cinnamate crosslinking network fixes the liquid crystal orientation, so that the polymer exhibits adhesion properties similar to those of linear polymers, which is convenient for combining with other substrate materials to construct composite devices. Both dual dynamic covalent networks can be dissociated after molding, making the liquid crystal film material recyclable and reusable.

[0109] A fifth aspect of the present invention discloses a method for applying programmable photodeformation of a liquid crystal film material, comprising the following steps:

[0110] Step 1: Use a light intensity of 50 mW / cm 2 , ultraviolet light with a wavelength of 365 nm irradiates the polymer, and under the action of external force, the polymer is deformed into the desired temporary shape;

[0111] Step 2: Maintain the deformation and use a light intensity of 50 mW / cm 2 , the polymer was irradiated with green light of wavelength 530 nm for 3 min, and the polymer could maintain the temporary shape;

[0112] Step 3: Irradiate the polymer again with 365 nm UV light of the same intensity, and the irradiated position of the polymer will return to its original shape.

[0113] Steps 1 to 3 can be repeated multiple times.

[0114] The sixth aspect of the present invention discloses a reversible photodeformation application method of a liquid crystal film material, comprising the following steps:

[0115] Step 1: Orientation by applying a stress field during processing;

[0116] Step 2: Use 50 mW / cm 2 , when ultraviolet light with a wavelength of 365 nm is irradiated on the sample, the illuminated position of the sample will bend away from the light source;

[0117] Step 3: Use 50 mW / cm 2 When green light with a wavelength of 530 nm is irradiated on the sample, the bent sample will return to its straight state.

[0118] Steps 2 and 3 can be repeated multiple times.

[0119] A seventh aspect of the present invention discloses a microfluidic chip, comprising:

[0120] A substrate, comprising an injection port and a groove communicating with the injection port;

[0121] Liquid crystal polymer film material, made of azobenzene liquid crystal polymer material and attached to a substrate;

[0122] The liquid crystal polymer film material at least partially covers the groove to form a closed channel with the groove, so that the microfluid can be driven through the closed channel under the Laplace pressure difference generated by the asymmetric photoinduced deformation of the closed channel.

[0123] The microfluidic chip made of the liquid crystal film material of the present invention and the microfluidic device containing the microfluidic chip can programmatically control the flow path, speed and mixing of the microfluid by controlling the intensity, direction and mode of light illumination, thereby realizing complex laboratory operations. The deformation and recovery of the liquid crystal polymer film material are reversible, and the microfluidic chip and the device can be used multiple times without losing their functions, thereby improving the repeatability and reliability of the experiment.

[0124] The following will explain through more specific implementation methods.

[0125] Embodiment 1:

[0126] Example 1 is an azobenzene liquid crystal polymer material prepared by using CAB monomer, CABO monomer and CA monomer, and the specific preparation method is as follows.

[0127] Ring-opening polymerization: CABO monomer (0.1 g, 0.2 mmol) and CAB monomer (0.375 g, 0.6 mmol) were added to a 10 mL Hiddink bottle according to the feed ratio of CAB monomer, CABO monomer and CA monomer of 3:1:1, and vacuum-nitrogen-vacuum was repeated three times. In an anhydrous and oxygen-free environment, 0.8 ml of anhydrous CH2Cl2 dissolved in CA monomer (0.051 g, 0.2 mmol) was injected into the Hiddink bottle with a syringe, and then 0.2 mL (1 mg / mL) of CH2Cl2 solution dissolved in Grubbs II generation catalyst was injected, and the reaction was carried out at 45 °C for 2 h. After the polymerization reaction was completed, 10 mL of CH2Cl2 was added to the Hiddink bottle, and the solution was dropped into methanol for precipitation. After filtration, an orange-yellow solid product (0.489 g, 93%) of linear azobenzene liquid crystal polymer material precursor L-PCABxOyCAz was obtained. Among them, after CAB monomer, CABO monomer, CA monomer, Grubbs II generation catalyst and solvent are mixed, the total concentration of CAB monomer, CABO monomer and CA monomer is 1 mmol / mL, and the molar ratio of CAB monomer, CABO monomer and CA monomer to Grubbs II generation catalyst is 1000:1.

[0128] Cross-linking polymerization: Take 60 mg / L L-PCABxOyCAz and prepare a toluene solution with a concentration of 6 wt%. After the linear polymer L-PCABxOyCAz is completely dissolved, filter it using a 1 mL syringe with a filter plug. Prepare a toluene solution of maleimide and ultrasonically treat it for 40 min. Mix it with the filtered linear azobenzene liquid crystal polymer material precursor L-PCABxOyCAz, stir it in an ice water bath for 2 hours, and then drop the mixed solution on a 4 cm×4 cm glass substrate and spread it flat. After toluene evaporates, a film is formed, and then annealed at 80 °C for 3 hours, and then immersed in ethanol to make the film fall off, to obtain the azobenzene liquid crystal polymer material of Example 1.

[0129] Embodiment 2:

[0130] Example 2 is an azobenzene liquid crystal polymer material prepared by using CAB monomer, CABO monomer and CA monomer. The only difference between Example 2 and Example 1 is that the feed ratio of CAB monomer, CABO monomer and CA monomer is 3:1:0.5.

[0131] Embodiment 3:

[0132] Example 3 is an azobenzene liquid crystal polymer material prepared by using CAB monomer, CABO monomer and CA monomer. The only difference between Example 3 and Example 1 is that the feed ratio of CAB monomer, CABO monomer and CA monomer is 3:1:2.

[0133] Embodiment 4:

[0134] Example 4 is an azobenzene liquid crystal polymer material prepared by using CAB monomer, CABO monomer and CA monomer. The only difference between Example 4 and Example 1 is that the feed ratio of CAB monomer, CABO monomer and CA monomer is 3:1:3.

[0135] The phase transition temperature of the azobenzene liquid crystal polymer materials of Examples 1-4 was tested by differential scanning calorimetry (DSC). The results were as follows: Figure 1-Figure 4 As shown. Figure 1-Figure 4 In the figure, with the horizontal axis as the reference, the curve farther from the horizontal axis is the cooling process, and the curve closer to the horizontal axis is the heating process; relative to the horizontal direction, the upward peak represents heat release, and the downward peak represents heat absorption. It can be seen that when the CA monomer feed ratio z is gradually reduced from 3 to 0.5, the second phase transition temperature of the azobenzene liquid crystal polymer material rises from 63°C to 84°C, and the first phase transition temperature is as low as 29°C. The phase transition temperatures of the azobenzene liquid crystal polymer material are all within the appropriate range, and the application of the azobenzene liquid crystal polymer material can be effectively guaranteed.

[0136] Comparative Example 1:

[0137] Comparative Example 1 is a side chain linear azobenzene liquid crystal polymer material PC9AB prepared using monomer C9AB.

[0138] .

[0139] The specific preparation method of comparative example 1 is as follows: in a beaker, 5 g of 4-cyanoaniline is dissolved in hydrochloric acid, 20 mL of an aqueous solution of 3 g of sodium nitrite is added, the reaction is stirred at low temperature for 2 hours, an aqueous solution formed by 4 g of phenol, 2 g of sodium hydroxide and 20 mL of water is added, sodium carbonate solution is added dropwise to adjust the pH value, the reaction is stirred at low temperature for 3 hours, hydrochloric acid is added dropwise to adjust the pH value to be acidic, solids are filtered out, and then recrystallized from ethanol to obtain the product 4′-cyano-4-hydroxyazobenzene. Subsequently, in a two-necked flask, 3 g of 4′-cyano-4-hydroxyazobenzene is dissolved in 20 mL of DMF, 2 g of potassium carbonate is added, and then 3 g of 9-bromo-1-nonanol is added, and the reaction is heated, stirred, condensed and refluxed for 4 hours. After the reactant is cooled to room temperature, distilled water is added and the crude product is filtered out. The crude product is then recrystallized from methanol to obtain the product 4′-(9-hydroxynonaneoxy)-4-cyanoazobenzene. Then, 1 g of 5-carboxyl-1-cyclooctene, 3 g of 4′-(9-hydroxynonyloxy)-4-cyanoazobenzene, 0.5 g of 4-dimethylaminopyridine, and 50 mL of anhydrous dichloromethane were added to a three-necked flask, and 20 mL of a dichloromethane solution of 2 g of N,N′-dicyclohexylcarbodiimide was added dropwise under argon protection. After the addition was complete, the reaction was carried out at room temperature for 48 h, and the solid was removed by filtration, washed with saturated brine, and the organic layer was concentrated to obtain a crude product. The crude product was purified by column chromatography and then recrystallized to obtain the monomer C9AB.

[0140] 0.5 g of monomer C9AB was dissolved in dichloromethane and added to a two-necked flask. A microinjector was used to add 200 μL of dichloromethane solution containing Grubbs catalyst, wherein the molar ratio of monomer to Grubbs catalyst was 1000: 1. Argon was protected and the reaction was carried out at 100°C for 0.5 h. 2 mL of vinyl ethyl ether was added to terminate the reaction. 2 mL of dichloromethane was added to dissolve the product, and then the solution was poured into methanol to precipitate the product, and the polymerization product was obtained by suction filtration.

[0141] Comparative Example 2:

[0142] Comparative Example 2 is an azobenzene liquid crystal polymer material prepared by using CAB monomer, CABO monomer and CA monomer. The only difference between it and Example 1 is that the feed ratio of CAB monomer, CABO monomer and CA monomer is 3:1:4. The phase transition temperature test was conducted on Comparative Example 2. The results show that the first phase transition temperature of Comparative Example 2 is only 23°C, and the liquid crystal polymer is in a liquid crystal state at room temperature, which may lead to a decrease in the stability of the material during temperature fluctuations, which is manifested as an increase in the disorder of the polymer chain, thereby reducing the mechanical properties.

[0143] Comparative Example 3:

[0144] Comparative Example 3 is an azobenzene liquid crystal polymer material prepared by using CAB monomer, CABO monomer and CA monomer. The only difference between it and Example 1 is that the feed ratio of CAB monomer, CABO monomer and CA monomer is 3:1:0.3. The phase transition temperature of Comparative Example 3 was tested. The results show that the second phase transition temperature of Comparative Example 3 is as high as 91°C. Due to the excessively high phase transition temperature, the liquid crystal polymer may not be able to maintain the liquid crystal phase within the normal operating temperature range, resulting in a decrease in its optical performance.

[0145] Application Example 1:

[0146] Application Example 1 is a liquid crystal film material prepared by using the azobenzene liquid crystal polymer material of Example 1. The specific preparation method is as follows.

[0147] Stress field orientation: a film made of azobenzene liquid crystal polymer material is placed on a mold with a curved surface;

[0148] Photo-crosslinking and orientation: A film made of azobenzene liquid crystal polymer material is irradiated with ultraviolet light with a wavelength of 312 nm to obtain a liquid crystal film material.

[0149] like Figure 7 As shown, when the liquid crystal film material is irradiated with 365nm ultraviolet light, the liquid crystal film material bends and deforms by about 90°; when the liquid crystal film material is irradiated with 530nm green light, the liquid crystal film material returns to its original state. This bending deformation-recovery cycle can be repeated 300 times, and the bending deformation of the liquid crystal film material remains unchanged.

[0150] Application Example 2:

[0151] In Application Example 2, the liquid crystal film material of Application Example 1 is further bonded to a PMMA substrate to obtain a composite device.

[0152] The liquid crystal film material obtained in Example 1 is thermally bonded to a PMMA substrate with a flow channel engraved thereon. Figure 8 As shown, adhesive-free bonding between the film and the substrate is possible due to the dynamic network.

[0153] Application Example 3:

[0154] In Application Example 3, the liquid crystal film material of Application Example 1 is further solid-state reshaped and recycled to form liquid crystal materials in various forms.

[0155] The liquid crystal film material obtained in Example 1 is heated to melt it again, or dissolved in an organic solvent, and then remolded by melting or solution method to form liquid crystal materials in various forms such as films and fibers. Their chemical composition and light responsiveness will not change. This process can be repeated multiple times.

[0156] Application Example 4:

[0157] Application Example 4 is a liquid crystal film material prepared by injection molding and photo-crosslinking the azobenzene liquid crystal polymer material of Examples 1-4. The specific preparation method is as follows.

[0158] Injection molding: The azobenzene liquid crystal polymer material of Example 1-4 is heated and melted and then molded by injection molding. First, the bottom mold is fixed and preheated, and then the liquid crystal polymer melt is injected into a film molding mold containing a vertical alignment layer through an injection port using an injection molding machine under a certain pressure, cooled to room temperature, and the mold is removed to obtain a liquid crystal polymer film;

[0159] Photo-crosslinking and orientation: A film made of azobenzene liquid crystal polymer material is irradiated with ultraviolet light with a wavelength of 312 nm to obtain a liquid crystal film material.

[0160] When the liquid crystal film material is exposed to ultraviolet light of 365nm, it bends and deforms; when the liquid crystal film material is exposed to green light of 530nm, it returns to its original shape. This bending deformation-recovery cycle can be repeated up to 150 times, and the deformation amount remains unchanged.

[0161] Application Comparative Example 1:

[0162] Application Comparative Example 1 is a liquid crystal film material prepared by using the azobenzene liquid crystal polymer material of Comparative Example 1, and the specific preparation method is as follows.

[0163] Stress field orientation: a film made of azobenzene liquid crystal polymer material is placed on a mold with a curved surface;

[0164] Photo-crosslinking and orientation: A film made of azobenzene liquid crystal polymer material is irradiated with ultraviolet light with a wavelength of 312 nm to obtain a liquid crystal film material.

[0165] like Figure 6As shown, when the liquid crystal film material is irradiated with 365nm ultraviolet light, the liquid crystal film material bends and deforms; when the liquid crystal film material is irradiated with 530nm green light, the liquid crystal film material returns to its original state. However, compared with the application example 1, the deformation amount of the application comparative example 1 is significantly smaller, and the deformation amount of the application example 1 is significantly improved.

[0166] Although the present invention has been illustrated and described with reference to certain preferred embodiments of the present invention, it should be understood by those skilled in the art that the above is a further detailed description of the present invention in conjunction with specific embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. Those skilled in the art may make various changes in form and details, including making several simple deductions or substitutions, without departing from the spirit and scope of the present invention.

Claims

1. An azobenzene liquid crystal polymer material, characterized in that: The azobenzene liquid crystal polymer material is obtained by a cross-linking reaction between an azobenzene liquid crystal polymer material precursor and a cross-linking agent, wherein the cross-linking reaction is a reaction between the furan group on the side chain of the azobenzene liquid crystal polymer material precursor and the cross-linking agent, and the azobenzene liquid crystal polymer material precursor is obtained by a ring-opening metathesis polymerization reaction between a CAB monomer, a CABO monomer and a CA monomer, wherein the CAB monomer has a structure shown in formula (I), the CABO monomer has a structure shown in formula (II), the CA monomer has a structure shown in formula (III), and the azobenzene liquid crystal polymer material has a structure shown in formula (IV): (Ⅰ); (Ⅱ); (Ⅲ); (Ⅳ); When the ring-opening metathesis polymerization reaction is carried out, the molar ratio of the CAB monomer, the CABO monomer and the CA monomer is x:y:z, wherein x=3, y=1, and the value range of z is 0.5-3.

2. An azobenzene liquid crystal polymer material according to claim 1, characterized in that: The azobenzene liquid crystal polymer material precursor has a structure shown in formula (V): (Ⅴ)。 3. The azobenzene liquid crystal polymer material according to claim 1, characterized in that: The cross-linking agent has a structure shown in formula (VI): (Ⅵ)。 4. A method for preparing an azobenzene liquid crystal polymer material as claimed in any one of claims 1 to 3, characterized in that: The steps include: Ring-opening polymerization: CAB monomer, CABO monomer, CA monomer, Grubbs II generation catalyst and solvent are mixed to carry out ring-opening polymerization reaction to generate azobenzene liquid crystal polymer material precursor; Cross-linking polymerization: mixing the azobenzene liquid crystal polymer material precursor with a cross-linking agent to obtain the azobenzene liquid crystal polymer material after a cross-linking reaction.

5. The method for preparing an azobenzene liquid crystal polymer material according to claim 4, characterized in that: In the ring-opening polymerization step, after the CAB monomer, the CABO monomer, the CA monomer, the Grubbs II generation catalyst and the solvent are mixed, the total concentration of the CAB monomer, the CABO monomer and the CA monomer is 0.8-1.2 mmol / mL, and the molar ratio of the CAB monomer, the CABO monomer and the CA monomer to the Grubbs II generation catalyst is 900:1-1000:

1.

6. A liquid crystal film material, characterized in that: The liquid crystal film material is made of the azobenzene liquid crystal polymer material according to any one of claims 1 to 3.

7. A liquid crystal film material according to claim 6, characterized in that: The liquid crystal film material bends and deforms under the irradiation of ultraviolet light with a wavelength of 365nm, and recovers to its original state under the irradiation of green light with a wavelength of 530nm. After 300 cycles of bending and deformation-restoration, the bending deformation amount of the liquid crystal film material remains unchanged.

8. A method for preparing a liquid crystal thin film material as claimed in claim 6 or 7, characterized in that: The method comprises the following steps: stress field orientation: placing a film made of the azobenzene liquid crystal polymer material on a mold with a curved surface, so that the azobenzene liquid crystal polymer material is oriented in a stress field; Photo-crosslinking and orientation: The film made of the azobenzene liquid crystal polymer material is irradiated with ultraviolet light with a wavelength of 312 nm to perform photo-crosslinking and orientation, thereby obtaining the liquid crystal film material.

9. A method for preparing a liquid crystal thin film material according to claim 8, characterized in that: The intensity of the ultraviolet light is 20 mW / cm 2 -80mW / cm 2 .

10. A microfluidic chip, characterized in that: include: A substrate, comprising an injection port and a groove communicating with the injection port; A liquid crystal polymer film material, made from the azobenzene liquid crystal polymer material according to any one of claims 1 to 3, and attached to the substrate; The liquid crystal polymer film material at least partially covers the groove to form a closed channel with the groove, so that the microfluid can be driven through the closed channel under the Laplace pressure difference generated by the asymmetric photoinduced deformation of the closed channel.

11. A microfluidic device, characterized in that: Comprising the microfluidic chip as claimed in claim 10.

Citation Information

Patent Citations

  • Side chained linear azobenzene liquid crystal polymer material and preparation method thereof

    CN103087296A

  • Azobenzene and cinnamic acid ester group-containing side-chain-type liquid crystal polymer membrane material and synthetic method therefor

    CN103374125A